The Influence of Leadership Style And Work Motivation on Employee Performance of PT. BPR BKK TASIKMADU - Dewi, Rosita; Winarti, Winarti; Suhita, Damayanti (Solidaritas, 2024)
Leadership from an organizational leader is considered a pivotal and central factor in improving employee performance. The approach a leader can take to guide, motivate, and manage a team is through leadership style. Additionally, work motivation is also a driving factor for enhancing employee performance in an organization or company. PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch has experienced changes in target achievements each period, which sparked the researcher's interest in conducting this study. The aim of this research is to determine the effect of leadership style and work motivation on employee performance at PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch, Karanganyar Regency. This study uses a quantitative research method, utilizing leadership style theory by Kartono and Kartini, work motivation theory by Abraham Maslow, and employee performance theory by Robbins. The research was conducted at PT. BPR BKK TASIKMADU (Perseroda) Jumantono branch, Karanganyar Regency, involving the entire population of 16 employees. Data analysis techniques employed multiple linear regression. The results indicate a strong relationship between leadership style and work motivation. Leadership style obtained a t-value of 6.085, work motivation a t-value of 2.727, meaning each variable significantly affects employee performance, and both leadership style and work motivation simultaneously affect employee performance with an F-value of 35.143. The conclusion of this study is that the variable with the strongest influence on employee performance is leadership style. Recommendations from this study are that leaders should guide employees who are struggling and implement risk management without applying excessive pressure, while understanding each employee's capabilities to achieve company goals. Leaders need to improve office security and ensure emergency preparedness so that employees feel safe and productive. Employees are expected to manage their time well, prioritize tasks, and work independently without direct supervision to maintain performance and productivity.